Advanced Gender Perspective as a Transversal Axis in the Cuban Academic Program of Journalism: An Action Research Approach - Rodríguez-Bazán, Grettel; Galañena-León, Yadán Crecencio; Ramos-Pérez, Amalia (Revista Electrónica Educare, 2023)
Aim. This paper proposes actions from the action-research approach, within the Cuban academic program of Journalism. Method. This study utilized qualitative methodologies including content analysis, expert interviews, and student focus groups. Results. The study proposed actions that gain in depth level as the academic years progress from the curricular, research, and extension perspectives. The actions contribute to mainstreaming the advanced gender perspective into the academic program. The analysis is conducted using the phases of the action research methodology, facilitating the involvement of students and researchers in communities where sexual and gender literacy is crucial. Conclusions. By immersing themselves in real social scenarios during their pre-professional practices, journalism students will not only address content that highlights gender discrimination but will also actively contribute as agents of change, advocating for equity and social justice.